Between two pandemics: Older, gay men's experiences across HIV/AIDS and COVID-19 - Ingrid Handlovsky; Tessa Wonsiak; Anthony T. Amato; Michael Halpin; Olivier Ferlatte; Hannah Kia (Elsevier, 2023)
Pandemics are a component of human life, and have had great bearing on the trajectory of human evolution. Historically, the biomedical aspects of pandemics have been overrepresented, but there is growing recognition of the degree to which pandemics are socially and culturally embedded, highlighting how virus perception is socially and politically informed. Older (50+), gay men represent a population who have experienced two global pandemics in their lifespans: HIV/AIDS and COVID-19. Although governments and health officials largely failed gay men during the HIV/AIDS pandemic, gay men represent an important source of pandemic information and their experiences have much to offer health professionals and policymakers. As such, a small but growing body of literature has compared gay men's experiences amidst the two pandemics. The current study drew on constructivist grounded theory methods to examine how living through the HIV/AIDS pandemic has influenced older gay men's perspectives of COVID-19. Twenty Canadian-based gay men aged 50+ participated in semi-structured interviews via Zoom. Analysis revealed three key processes: (1) uncertainty and the familiarity of loss, (2) witnessing pandemic inequities, and, (3) navigating constantly evolving (mis)information. We highlight the utility of this knowledge to informing future pandemic planning and policies.